2021
DOI: 10.1371/journal.pone.0245697
|View full text |Cite
|
Sign up to set email alerts
|

Wheat rust epidemics damage Ethiopian wheat production: A decade of field disease surveillance reveals national-scale trends in past outbreaks

Abstract: Wheat rusts are the key biological constraint to wheat production in Ethiopia—one of Africa’s largest wheat producing countries. The fungal diseases cause economic losses and threaten livelihoods of smallholder farmers. While it is known that wheat rust epidemics have occurred in Ethiopia, to date no systematic long-term analysis of past outbreaks has been available. We present results from one of the most comprehensive surveillance campaigns of wheat rusts in Africa. More than 13,000 fields have been surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The prevalence and intensity of the diseases were variable with location, distance from the river, crop type, variety, altitude range, and the growth stage of the crop. Temporal analysis indicated that a sigmoidal rise in disease levels during the wheat season and strong inter-annual variations [ 45 ]. While a simple logistic curve performs satisfactorily in predicting stem rust in some years but not outbreak patterns in other years [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence and intensity of the diseases were variable with location, distance from the river, crop type, variety, altitude range, and the growth stage of the crop. Temporal analysis indicated that a sigmoidal rise in disease levels during the wheat season and strong inter-annual variations [ 45 ]. While a simple logistic curve performs satisfactorily in predicting stem rust in some years but not outbreak patterns in other years [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Temporal analysis indicated that a sigmoidal rise in disease levels during the wheat season and strong inter-annual variations [ 45 ]. While a simple logistic curve performs satisfactorily in predicting stem rust in some years but not outbreak patterns in other years [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the temporal and spatial relationships between climate, disease, and yield give us the same insights, we can have a stronger belief in the generality of the hypothesized climate–disease–yield relationship. As one example, disease levels of stem rust and leaf rust on wheat are known not only to have increased with increasing temperatures due to climate change but also higher at low, warm elevations than at high, cold elevations (Meyer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Stripe or yellow rust (Puccinia striiformis f.sp. tritici) and leaf or brown rust (Puccinia triticina) is indeed a potential biotic restraint, damaging the crop and causing substantial economic losses worldwide (Ali et al 2017;Kumar et al 2020;Meyer et al 2021). The stripe rust is continuing to be a serious threat and dominant factor limiting yield potential in wheat globally (Chen et al 2014(Chen et al , 2020.…”
Section: Introductionmentioning
confidence: 99%